2017
DOI: 10.18520/cs/v113/i09/1746-1749
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Antioxidant Activity of Hydroxy-Quinoline Derivatives and their Delivery Via Boron Nitride Nanocage in Gas Phase and Solvent

Abstract: The antioxidant activity of hydroxy-quinoline derivatives was studied in gas phase and solvent. Results indicate that substituents in hydroxy-quinoline decrease the bond dissociation enthalpy and ionization potential values and thus increase the antioxidant activity of hydroxy-quinoline. Results also show that NHMe hydroxy-quinoline has the highest antioxidant activity. The ability and potential of boron nitride (B 36 N 36 ) nanocage in the delivery of hydroxy-quinoline derivatives via DFT method was studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, BN fullerene like cages have been found to improve the antioxidant activity of phenolic compounds through their adsorption on the external surface of the former. In this perspective [18], showed that B 36 N 36 can efficiently improve the antioxidant activity as well as the delivery of hydroxyquinoline derivatives. Analysis of the antioxidative mechanisms of a complex formed from the adsorption of apigenin on B 12 N 12 surface also revealed the improvement of radical scavenging activity of apigenin by B 12 N 12 [19].…”
mentioning
confidence: 98%
“…Moreover, BN fullerene like cages have been found to improve the antioxidant activity of phenolic compounds through their adsorption on the external surface of the former. In this perspective [18], showed that B 36 N 36 can efficiently improve the antioxidant activity as well as the delivery of hydroxyquinoline derivatives. Analysis of the antioxidative mechanisms of a complex formed from the adsorption of apigenin on B 12 N 12 surface also revealed the improvement of radical scavenging activity of apigenin by B 12 N 12 [19].…”
mentioning
confidence: 98%